Decoding the invisible forces of social connections - Cacioppo, Stephanie; Cacioppo, John T. (Frontiers in Integrative Neuroscience, 2012)
By its 20th anniversary, social neuroscience has witnessed an incredible rise in the number of studies demonstrating the effects of perceived social isolation (e.g., loneliness, ostracism), and inversely, the beneficial effects of social bonding (e.g., love, desire, attachment) on social perception, cognition, and behavior and on mental and physical health. The current review underscores the importance of two factors in this literature: (1) where an individual falls along the continuum of isolation/bonding from feelings of rejection and neglect to feelings of strong, stable, trusted social bonds, and (2) whether gauging an individual’s general feeling of social isolation/bonding or the specific feeling of isolation/bonding toward the person with whom the individual is interacting. Evidence shows that these factors are related to brain and cognition, including embodied social cognition – a system integrating past self-related actions from which simulation mechanisms can be used to access other people’s minds and anticipate their actions. The neurophysiological mechanisms underlying sensorimotor mapping between interacting individuals offers an empirical opportunity to investigate the interpersonal forces that operate on individuals at a distance. This multilevel integrative approach provides a valuable tool for investigating the brain networks responsible for understanding acute and chronic social disorders.